A framework for determination of actual costs in Islamic financing products - Mohd Noor, Azman; Haron, Muhamad Nasir (IIUM Press, 2016)
Islamic banking commonly considered as an alternative to the conventional banking system, conducts its business based on certain financial contracts in order to attain profit, while doing away with the element of interest (riba). Among the services offered by Islamic financial institutions (IFI) are financing products and fee-based services to generate profits free from interests and other non-permissible incomes. The fee-based services conducted by Islamic banks may raise some Shari’ah issues such as the practice of charging a fee on services related to loan (qard) facility. Similarly, in financing activities, the IFI also imposes some amount of compensation or related charges in the case of late payment or default events for such financing. This paper aims to discuss the mechanism to determine the calculation of such actual charges and fees from Shari’ah perspective. Nevertheless, this paper does not intend to discuss the issue of “pricing” for Islamic financial products to determine its sales price and profit margin. This paper proposes Shari’ah compliance parameters on the computation of the actual costs for some related financing products offered by Islamic financial institutions.